Factors of heterogeneity of mortgage refinancing in the Russian regions - E. A. Gafarova (Вестник университета)
During the period of soft monetary policy in Russia, there was heterogeneous regional growth of mortgage refinancing. Social, demographic, economic and financial indicators of the Russian regions explain interregional differences in mortgage refinancing. The article confirms the hypothesis about heterogeneity of effect of reducing average mortgage rate on mortgage refinancing in the Russian regions. Empirical estimates have been obtained by panel vector autoregression for groups of regions depending on the average income of population and average housing prices. The greatest increase of mortgage refinancing reduction of mortgage rates occurred in groups of regions with highand middle-income levels and liquid housing market. When mortgage-lending conditions are relaxed, regions with low average per capita incomes benefit least from mortgage refinancing.